(untitled) (Sains Humanika, 2020)
In global context, women make up the majority of students in academic institutions but are far less involved in manufacturing academic courses and work in the manufacturing sector. There are several reasons for this. There is a general perception among women that manufacturing carries a high risk of danger. Additionally, there are some tasks in the manufacturing sector that women are often physically unable to perform, such as those in the machinery, industrial equipment and automotive sector. The arrival of Industry 4.0 technology in the manufacturing sector, however, is likely to result in a decline in physical and onerous duties—overtly physical jobs could be replaced by automation and robotics. The cognitive abilities required for the development and implementation of full automation present vast opportunities for women. This paper aims to explore the strengths, weaknesses, opportunities and threats (SWOT) presented by women employment in the Industry 4.0 manufacturing sector. Thirty pieces of literature related to women employed in the manufacturing sector are reviewed. SWOT analysis is derived from the solo-coding process using ATLAS.ti. The results are found through qualitative thematic analysis and reveal that the weaknesses of and threats posed by women employment in the manufacturing sector could be outweighed by the strengths of and opportunities provided by Industry 4.0. This SWOT analysis contributes to the literature by providing a greater understanding of women employment in the Industry 4.0 manufacturing sector.